Possible Association between the Quantity of Peri-implant Crevicular Fluid, Clinical Indices, and the Dimensions of Endosseous Implants - Onurcem Duruel; Samir Goyushov; Nil Yakar; Güliz Nigar Güncü; Erdem Karabulut; Tolga Fikret Tözüm (eJournal of Oral Maxillofacial Research, 2022)
Objectives: The objectives of this clinical observational study are to measure peri-implant crevicular fluid volume based on dental implant diameter and length, and to evaluate the possible relationship between peri-implant crevicular fluid/gingival crevicular fluid volumes and clinical periodontal indices.